Foucault’un İktidar Görüşleri Işığında Erdal Öz’ün Yaralısın Romanı / Yaralisin, the Novel by Erdal Oz, in the Light of Foucault’s Power Theory - Üstün, Koray (Journal of History Culture and Art Research, 2017)
Abstract In the light of the power concepts theorized by Michel Foucault, this article investigates Erdal Oz’s novel Yaralisin (You’re Wounded). Foucault’s power structure that systematized in Subject and Power (1961), History of Sexuality (1984), Birth of Prison (1975), The Birth of Biopolitics (2004), has similarities with crime production that the novel reflects. Accordingly, individuals are being standardized in the prison through programs, strategies and technics that the power structure determined. In this process, there is no direct enforcement on the individual. The power structure connects the individual to itself through knowledge and body. In Oz’s novel the subject depending on space changing are being standardized and transformed into the “Nuri” character, as we read in the text. At the base of becoming standard individual through lost of identity, there is crime production. As for crime production, it takes shape in accordance with space. In the novel, space dependent suffering, inflicted on individuals, places the subject on a hierarchical plane, as Foucault has also indicated, and brings an end to existence. The power structure, cutting off the individual from his private space, taking him first into the interrogation room, and then to the prison, has made him a part of the system and has objectified him. The digestive effect of the power structure has become even more concrete with the presence of the second person narrator within the narrative plane; depersonalization has taken place within the new order. Öz Bu makalede Michel Foucault’un kuramsallaştırdığı iktidar kavramı ışığında Erdal Öz’ün Yaralısın romanı incelenmiştir. Foucault’nun Özne ve İktidar (1961), Cinselliğin Tarihi (1984), Hapishanenin Doğuşu (1975), Biyopolitikanın Doğuşu (2004) gibi kitaplarında sistemleştirdiği iktidar, romanda aktarılan suç üretimi ile paralellik taşımaktadır. Bireyler, iktidar tarafından belirlenen program, strateji ve tekniklerle hapishanelerde tek tipleştirilmektedir. Bu süreçte bireyler üzerine doğrudan bir yaptırım uygulanmaz; iktidar, bilgi ve beden yönetimi üzerinden bireyi kendine bağlar. Öz’ün romanında da uzamsal değişimlere bağlı olarak tekil özneler, tek tipleştirilerek metindeki karşılığıyla “Nuri”lere dönüşür. Bireyin kendi kimliğini yitirerek tek tipleşmesinin temelinde suç üretimi vardır. Suç üretimi ise uzama göre şekillenir. Romanda uzama göre değişen çektirilen azaplar, Foucault’un da belirttiği gibi özneyi hiyerarşik düzleme yerleştirir ve varoluşu sona erdirir. İktidar, özneyi kişisel mekânından ayırıp önce sorgu odasına ardından da hapishaneye götürerek onu düzenin bir parçası hâline getirmiş ve nesneleştirmiştir. İktidarın sindirici etkisi, anlatı düzlemindeki ikinci tekil anlatıcının varlığıyla daha da somutlaşmış; kurulan düzen içerisinde özne yitimi gerçekleşmiştir.